OPTIMASI PEMANFAATAN ENERGI AMPAS DI PABRIK GULA - Saechu, Muhammad (Jurnal Teknik Kimia, 2009)
Availibility of world fossil energi will continue scarce and progressively costly. The situation will affect to sugar production cost, specially at SF which still insuffiency of bagasse and burn oil. Insuffiency of bagasse in SF righteously can overcome because sugar cane have enough bagasse content for boiler fuel, with balance installation, efficient equipments, amount and quality of sugar cane milled which is adequate, hence in SF can be obtained excess of bagasse or energy which is useful for raw material of industry.Key words :Energy crisis, sugar factory (SF), cane bagasse, steam generation, steam use, energy efficiency.